FACTORS INFLUENCING INCREASING INTEREST IN TECHNICAL EDUCATION - AZALTOVICOVA, Michaela; TOMKOVA, Viera (Journal of Technology and Information Education, 2020)
The paper reflects the partial results of the inquiry focused on the pupils of primary schools and the factors that influence their interest in technical education. Despite the high demand from employers for technically skilled graduates of secondary vocational schools and universities, the interest of pupils in technical professions and technical education continues to decline. This is despite the research that shows that science perceives science (natural science) and technology positively because it realizes that science and technology make their lives more comfortable and easier.
Keywords: technical education; increasing interest; technic; education; profesional orientation of pupils